Academic Complaint Management Simulation Using the Trello Platform as a Real-Time Collaboration Tool - risna; Mida Herlina; Jumiati; Nazwa Risanti; Nafiatus Airya (INSTALL: Information System and Technology Journal, 2025)
The development of information technology is driving improvements in services in higher education, including how to handle complaints about facilities and infrastructure. However, many campuses, including UINSI Samarinda, do not yet have a clear and effective complaint system. The purpose of this study was to create and test a prototype academic complaint system based on the Trello project management platform, which uses a project-based learning approach. This system manages each report as a structured "micro-project." A four-week simulation case study with 20 students and administrators was used. In the simulation, data was collected through observations, satisfaction questionnaires, and analysis of activity on the Trello board. The simulation results showed that, with an average completion time of 21 days, the use of Trello improved complaint handling efficiency, increased workflow transparency, and enhanced direct collaboration between students and instructors. Butler Automation and other types of automation have been shown to assist with scheduling and task reminders. Therefore, Trello can be transformed into a responsive, visual, and easy-to-use campus complaint system. Furthermore, it offers a replicable model to help other universities digitalize their campus services.